Teaching sensory perceptions: An investigative class - Silva, Eptácio Neco da; Leal, Amanda Fernandes; Alves, Antônio Celso da Silva; Teodoro, Wilton Linhares; Brito, Francisco Pereira de; Soares , Alvenisa Fernandes Costa; Carvalho, Millena Raimunda Martins de Almeida; Soares, Antonia Nádia Viana; Soares, Gualberto de Abreu (Seven Editora, 2023)
All sensory processes begin with stimuli, which represent a form of energy, and a sensory cell converts this energy into a change in the membrane potential, regulating the production of action potentials in the central nervous system, whose encoding results in sensation. The general objective of this work is to report an experience in the development of an investigative teaching sequence (CES) on sensory perception of sight and taste with students of the 3rd grade of high school. The SEI was developed in 4 classes, where each one lasted 50 minutes and the materials used were: notebook and cell phone, to enable remote activities; fruits, sugar, drinking water and a spoon for practical activities; pen and tape for identification of materials. And virtual resources were used, such as: google classroom, google meet, google forms. CES raised the following problem question: Can the taste of food be altered by the sense of sight? During the application of the Investigative Didactic Sequence, it was observed that in the beginning the students were not motivated and were even anxious, since they wanted the answers ready. However, the characteristics of teaching by investigation with the participation of students were observed, a participation that grew during the activities. DOI:https://doi.org/10.56238/sevened2023.006-031